COVID-19 in pediatrics: an integrative review (Research, Society and Development, 2020)
Objective: To analyze the scientific literature that deals with the clinical, laboratory and radiological behavior of COVID-19 in the pediatric population. Methodology: This is an integrative literature review. The sample was selected through the PubMed, ScienceDirect, SciELO and LILACS databases, using the descriptors (("COVID-19" OR "SARS COV 2") AND Child). Results: 11 articles made up the result of this study. As for clinical behavior, signs and symptoms are mild and the most common were fever, cough and some gastrointestinal symptom. As for laboratory changes, leukopenia, neutropenia and increased C-reactive protein were the most frequent. Finally, regarding radiological findings, studies describe ground-glass opacity in most cases. An important finding pointed out by the studies was that, even after the removal of the virus from the respiratory tract, viral gastrointestinal infection and the potential fecal-oral transmission can continue. Conclusion: Cases of COVID-19 infection in pediatrics are still underreported when compared to cases in adults. Further studies are needed for a better understanding of the theme involving pediatric patients, in order to support the care process.